Recent advances in mineral processing plant design - Malhotra, Deepak (Society for Mining, Metallurgy, & Exploration, 2009)
The key to building better and more reliable plants is staying abreast of new technologies and equipment improvements. Whether you're an aspiring engineering student or a seasoned practitioner, you won't find a more comprehensive or more up-to-date resource than Recent Advances in Mineral Processing Plant Design. A compilation of engaging and insightful papers from the prestigious 2009 plant design conference, this volume is a sequel to Mineral Processing Plant Design, Practice, and Control, an industry standard published in 2002.